PENGARUH INTENSITAS ASET TETAP DAN RETURN ON ASSET TERHADAP TINDAKAN PENGHINDARAN PAJAK - Rusmanto -; Indra Saputra; Yudha Rusmida (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2020)
Abstract. The purpose of this study is to empirically prove the effect of fixed asset intensity and return on assets on tax avoidance in the mining and mining service sector listed on the Indonesia Stock Exchange for the 2016-2018 period. The sample in this study was obtained by purposive sampling method.